2014
DOI: 10.1093/treephys/tpu019
|View full text |Cite
|
Sign up to set email alerts
|

Root diameter variations explained by anatomy and phylogeny of 50 tropical and temperate tree species

Abstract: Root diameter, a critical indicator of root physiological function, varies greatly among tree species, but the underlying mechanism of this high variability is unclear. Here, we sampled 50 tree species across tropical and temperate zones in China, and measured root morphological and anatomical traits along the first five branch orders in each species. Our objectives were (i) to reveal the relationships between root diameter, cortical thickness and stele diameter among tree species in tropical and temperate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 62 publications
13
92
4
1
Order By: Relevance
“…However, information on radial variation in root xylem anatomical and hydraulic properties is yet very limited. Several studies separating root branching orders showed that conduit diameter tends to increase toward higher root orders, in agreement with our findings (Valenzuela-Estrada et al, 2008; Huang et al, 2010; Long et al, 2013; Gu et al, 2014), while others, however, failed to detect a radial conduit widening from the pith to the bark in roots (Dunham et al, 2007; Peterson et al, 2007; Lintunen and Kalliokoski, 2010). This may suggest that the radial pattern of xylem anatomy in woody roots is often overlain by adaptive responses to locally varying mechanical requirements (Christensen-Dalsgaard et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…However, information on radial variation in root xylem anatomical and hydraulic properties is yet very limited. Several studies separating root branching orders showed that conduit diameter tends to increase toward higher root orders, in agreement with our findings (Valenzuela-Estrada et al, 2008; Huang et al, 2010; Long et al, 2013; Gu et al, 2014), while others, however, failed to detect a radial conduit widening from the pith to the bark in roots (Dunham et al, 2007; Peterson et al, 2007; Lintunen and Kalliokoski, 2010). This may suggest that the radial pattern of xylem anatomy in woody roots is often overlain by adaptive responses to locally varying mechanical requirements (Christensen-Dalsgaard et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…This is of special importance, because our present study indicated that the higher storage temperatures (except for −3°C) had rather a negative impact on cortical tissue proportion, a parameter which is most sensitive to environmental changes (Gu et al 2014). Moreover, N concentration was positively correlated with the percentage of roots with primary development and cortical tissue.…”
Section: Discussionmentioning
confidence: 55%
“…; Gu et al . ). Our study further demonstrates that contrasting climatic and soil variables relate to changes in distinct fine‐root traits.…”
Section: Discussionmentioning
confidence: 97%
“…Gu et al . () observed for instance among 50 tropical and temperate tree species that tropical trees have on average thicker fine‐roots with lower tissue density and higher SRL than temperate trees. Chen et al .…”
Section: Introductionmentioning
confidence: 99%